Direct Answers in Google Search Results - Strzelecki, Artur; Rutecka, Paulina (IEEE access, 2020)
This study aims to explore Google's new "featured snippet" (a direct answer that appears in web search results) to better understand the method of extracting and displaying such answers above regular ranked results. The motivation for the study was to investigate form, structure, and relation to query, content, and domain of the direct answer. This study utilized a dataset of 743,798 keywords and the displayed direct answers. It also included web search data for every direct answer, e.g. resulting domain, full URL address and its original ranking, content of the direct answer, and competition (measured as the number of monthly searches for every query). The main finding concerns the form of construction of keywords used in the website content. Keywords should be built in the form of short, two-to-four-word sentences comprising the subject and its attribute. Using relative pronouns, articles, and prepositions, as well as using questions as queries, can help to properly define a query and display the best direct answer. The dataset is relatively small compared to the volume of searches made daily. No other factors were extracted from the URL, and all data concerned the Google search engine only. Implications for webmasters include: keywords used in website content should be close to grammar forms used in queries; use keywords in URLs; write a comprehensive introduction section on the webpage; and use tables and lists HTML markup. The main objective of this study was to examine the structure of the user's queries which caused in appearing of direct answers. It is comprehensive and based on real data used by web search engine users. The data used to support the findings have been deposited in the Zenodo repository ( https://doi.org/10.5281/zenodo.3541092 ).